Atypical Reye syndrome: three cases of a problem that pediatricians should consider and remember - Ferretti, Serena; Gatto, Antonio; Curatola, Antonietta; Pansini, Valeria; Graglia, Benedetta; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Reye syndrome is a rare acquired metabolic disorder appearing almost always during childhood. Its aetiopathogenesis, although controversial, is partially understood. The classical disease is typically anticipated by a viral infection with 3-5 days of well-being before the onset of symptoms, while the biochemical explanation of the clinical picture is a mitochondrial metabolism disorder, which leads to a metabolic failure of different tissues, especially the liver. Hypothetically, an atypical response to the preceding viral infection may cause the syndrome and host genetic factors and different exogenous agents, such as toxic substances and drugs, may play a critical role in this process. Reye syndrome occurs with vomiting, liver dysfunction and acute encephalopathy, characterized by lack of inflammatory signs, but associated with increase of intracranial pressure and brain swelling. Moreover, renal and cardiac dysfunction can occur. Metabolic acidosis is always  detected, but diagnostic criteria are not specific. Therapeutic strategies are predominantly symptomatic, in order to manage the clinical and metabolic dysfunctions. Case reports: We describe three cases of children affected by Reye syndrome with some atypical features, characterized by no intake of potentially trigger substances, transient hematological changes and dissociation between hepatic metabolic impairment, severe electroencephalographic slowdown and slightly altered neurological examination. Conclusions: The syndrome prognosis is related to the stage of the syndrome and the rapidity and the adequateness of intensive care treatments. The analysis of the patients leads to a greater awareness of the difficult diagnosis of this not well completely known syndrome.